KEANEKARAGAMAN DAN KEMELIMPAHAN ODONATA DI KAWASAN HULU ALIRAN SUNGAI KALIBENDO, BANYUWANGI - Magdalena Putri Nugrahani; Rizqi Dwi Firmansyah; Susintowati Susintowati (JURNAL BIOSENSE, 2022)
Odonata is an insect that plays an important role in the balance of the ecosystem, acting as predators. Most of Odonata’s life is in the water in form of larvae. Odonata occupies some specific habitat types of waters. This study aims to determine the diversity, abundance, and distribution of Odonata (dragonflies and damselflies) in the upstream area of Kalibendo river, Banyuwangi. The research method used is River Tracking method with 4 points of observation which each has a radius of 1,25 km. Based on the result, 13 species of dragonfly are found 7 species dragonfly (Anisoptera) and 6 species of damselflies (Zygoptera). Diversity index (H’) of Odonata on the four observation points are low. Relative abundance (KR) species Vestalis luctuosa was the highest (48,522%), while the lowest was Potamarcha congener and Pseudagrion pruinosum (0,053%). The distribution of Odonata in the Kalibendo river basin area, all of which belong to the uniform and clumped category.